Perinatal antidepressant use and breastfeeding outcomes: Findings from the Norwegian Mother, Father and Child Cohort Study - Luke E. Grzeskowiak; Moni R. Saha; Hedvig Nordeng; Eivind Ystrom; Lisa H. Amir (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Antidepressant use is common in the perinatal period, but there are concerns that it can negatively impact on breastfeeding outcomes. The aim of this study was to examine the effects of perinatal antidepressant use on breastfeeding initiation and duration. Material and methods This was a retrospective analysis of 80 882 mother–infant dyads in the Norwegian Mother, Father and Child Cohort Study (MoBa). Women were first classified according to self‐reported mental disorders and timing of antidepressant use before and/or after gestational week 28 (i.e., early‐mid–gestation and/or late‐gestation use). We subsequently classified women according to self‐reported mental disorders and antidepressant use postpartum and whether antidepressants were continued from late gestation or were new/restarted. Breastfeeding outcomes included breastfeeding initiation as well as predominant or any breastfeeding and abrupt breastfeeding discontinuation until 6 months. Results Late‐gestation antidepressant use was associated with a reduced likelihood of breastfeeding initiation (adjusted relative risk [aRR] 0.93; 95% confidence interval [CI] 0.90–0.97) but not predominant (aRR 0.96; 95% CI 0.67–1.39) or any (aRR 1.00; 95% CI 0.93–1.07) breastfeeding at 6 months compared with unexposed women with mental disorders. When examined according to postnatal antidepressant use, no differences in predominant (aRR 0.94; 95% CI 0.60–1.48) or any breastfeeding (aRR 0.99; 95% CI 0.91–1.07) at 6 months were evident among women who continued antidepressant use from late gestation into the postpartum period compared with unexposed women with mental disorders. In contrast, new/restarted antidepressant use postpartum was associated with a reduced likelihood of predominant (aRR 0.37; 95% CI 0.22–0.61) and any (aRR 0.49; 95% CI 0.42–0.56) breastfeeding at 6 months, as well as increased risk of abrupt breastfeeding discontinuation (aRR 2.64; 95% CI 2.07–3.37) compared with the unexposed women with mental disorders. Conclusions A complex relation exists between depression, antidepressant use, and breastfeeding outcomes. Antidepressant use in late pregnancy was associated with a reduced likelihood of breastfeeding initiation but not breastfeeding duration or exclusivity. In contrast, initiating or restarting antidepressants postpartum was associated with poorer breastfeeding outcomes. Overall, women taking antidepressants and women with a mental disorder may benefit from additional education and support to improve breastfeeding rates and promote maternal and infant health and wellbeing.